The digital routes of human smuggling?:Evidence from the UK - Antonopoulos, Georgios (2019)
There are justified concerns but little empirical evidence about the implications of the use of information and communication technologies (ICT) in the business of human smuggling. The knowledge base on the use of ICT in human smuggling has rarely gone beyond the rather generic observation that the Internet and mobile technologies are available to and are used by both smugglers and migrants, and there is a concrete knowledge gap regarding the extent and the mode in which the use of ICT is integrated in the process of smuggling. In this paper, which is part of a wider research effort concerned with the role of the Internet in human smuggling in the European Union, we interrogate the outlook and implications of the use of contemporary mobile technology and of social media in the organisation and conduct of human smuggling to the UK